Analysis of Supporting Factors for the Successfull of the SMA Muhammadiyah 9 Building Project - Damayga Ridlo Baihaqi; Diah Ayu Restuti Wulandari (LPPM NAROTAMA UNIVERSITY, Indonesia, 2022)
Problems in the field can also be obstacles, for example delays in ordering materials, damage to equipment that takes time to repair or renew tools, and disruption of productivity in projects caused by delays in disbursing funds from the owner. This writing aims to identify the factors that support the success of construction projects, and the dominant factors that support the success of construction projects. The method used in the research to support the success of this construction project is using the Analysis Hierarchy Process (AHP) method. The decision-making method developed for prioritizing several alternatives when several criteria must be considered, as well as allowing decision makers to organize complex problems into a hierarchical form or an integrated set of levels. The results of this study can be concluded that quality is one of the factors the most dominant in supporting the success of the Muhammadiyah High School Building construction project with a weight value of 0.507. The second factor is time with a weight of 0.198, the third factor is human with a weight of 0.174, the fourth factor is communication with a weight of 0.066, and the fifth factor is cost with a weight of 0.055. The first success factor of the project is the quality control factor of material quality with a weight value of 0.390. Second, the time factor for the use of goods with a weight value of 0.114. Third, namely the human factor of disciplined workers with a weight value of 0.099. Fourth, the quality factor of labor expertise with a weight value of 0.074. Fifth, the project monitoring time factor with a weight value of 0.047.